Rational Type Contraction in b-Metric Spaces and Common Coupled Fixed Point Theorems - Tiwari, Surendra Kumar; Ganvir, Jayant Prakash; Sahani, Suresh Kumar (Journal of Nepal Mathematical Society, 2023)
The intention of this script is to construct and obtain some new results for common coupled fixed points in b-metric space for a pair of mappings satisfying rational type contraction. The present results extend, modify, and generalize the existing literature. The results are verified with the help of suitable examples.